The Effect of Price Sensitivity on Purchase Intention is Mediated by Advocacy and Emotion on Consumers of Pharmaceutical Companies in Jakarta - Akhmad Afendi (Journal of Social Research, 2023)
The development of industry in Indonesia, especially in the pharmaceutical and drug sector, has created increasingly fierce competition, where currently the world of public health businesses, pharmaceutical companies or drug companies are commercial business companies that focus on researching, developing, and distributing drugs, especially in terms of health. This study aims to analyze the effect of Price Sensitivity on Purchase Intention mediated by Advertisement and Emotion. The data used in this study is primary data sourced from observations, reports and questionnaires. The research samples were consumers of pharmaceutical companies in Jakarta such as PT Parit Padang Global, PT Kimia Farma, and PT Kalbe Farma in Jabodetabek using the purposive sampling method so that 170 respondents were sampled. Data analysis used to test hypotheses using structural equation modeling (SEM) analysis methods with program analysis of moment structure (AMOS). The results showed that Emotion has an effect on purchase intention. The processed results obtained an estimated value of 0.593 and a p-value of 0.000 which is less than the p-value requirement of 0.05.